2003
DOI: 10.1002/bip.10477
|View full text |Cite
|
Sign up to set email alerts
|

Binding of copper(II) ions to the polyproline II helices of PEVK modules of the giant elastic protein titin as revealed by ESI‐MS, CD, and NMR

Abstract: Titin, a family of giant elastic proteins, constitutes an elastic sarcomere matrix in striated muscle. In the I-band region of the sarcomere, the titin PEVK segment acts as a molecular spring to generate elasticity as well as sites of adhesion with parallel thin filaments. Previously, we reported that PEVK consists of tandem repeats of 28 residue modules and that the "polyproline II-coil" motif is the fundamental conformational motif of the PEVK module. In order to characterize the factors that may affect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…This ion has been found to be capable of binding both the ring N of the prolyl residue in a series of substituted polyproline 36 and PPII regions of synthesized polypeptides. 37 Besides, it has been reported 36 that Cu 2C leads to a conformational change of PPII regions to other secondary structure elements (i.e. b-turn-like structure) on increasing concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This ion has been found to be capable of binding both the ring N of the prolyl residue in a series of substituted polyproline 36 and PPII regions of synthesized polypeptides. 37 Besides, it has been reported 36 that Cu 2C leads to a conformational change of PPII regions to other secondary structure elements (i.e. b-turn-like structure) on increasing concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Cu 2+ binds to specific regions in the PEVK repeat and alters the structure from a polyproline helix to β-turn (Ma and Wang, 2003a). Additionally, changes in environment, such as dielectric constant or temperature, transition the PEVK structure from a polyproline helix to a β turn or to a random coil (Ma et al, 2001; Ma and Wang, 2003a,b). Likewise, protein binding can significantly influence PEVK structure and therefore elasticity (Ma and Wang, 2002; Ma et al, 2006).…”
Section: Titin Architecture Within the Sarcomerementioning
confidence: 99%
“…Proline is the only amino acid that has been used as a ligand in asymmetric catalysis,26 and the binding of copper (II) ions in the PLP II helices in proteins is well documented 27. In addition, oligoprolines are used as ligands in metal complexes in electrochemical reactions, where it has been observed that the redox potential28 of the ferrocenyl group attached to the oligoproline chains depends on the sequence and length of oligoprolines. Finally, a recent study showed that a 50% proline‐containing cell‐penetrating hexapeptide exhibited enhanced translocation across the cytoplasmic membrane as Au‐NP transporting cargo 29…”
Section: Introductionmentioning
confidence: 99%